Integration Of Sufistic Character Values In The Curriculum Of Subjects In Mts Islamic Boarding School Jember - Nurul Anam (STAIFAS-Press, 2021)
The spread of radical or terrorist character values ​​has begun to occur in many Islamic educational institutions. This fact must be a concern for Islamic educational institutions, including the MTs Islamic Boarding School (IBS) which is under the auspices of Islamic boarding schools. The IBS-based MTs Al-Qodiri 1 Jember has made efforts to overcome this, one of which is by integrating Sufi values ​​in the subject curriculum. To describe the integration process in the institution, the researchers used a qualitative research approach and the type of case study research. The results of his research indicate that the integration of Sufistic values ​​in subjects at MTs IBS has been carried out well. Sufistic values ​​that have been integrated consist of the values ​​of sincerity, simplicity, ukhuwah Islamiyah, independence and discipline. This integration process is carried out by means of all Sufistic values ​​being internalized in several focus or sub-focus discussions related to other values. The integration of these character values ​​into the subject curriculum is carried out in three aspects, namely into the syllabus, lesson plans and the learning process. This integration model can make it easier for teachers to carry out the process of planting, forming and habituation of Sufi values ​​in the daily lives of students. Penyebaran nilai-nilai karakter radikalis atau teroris sudah mulai banyak terjadi di lembaga pendidikan Islam. Kenyataan ini harus menjadi perhatian bagi lembaga pendidikan Islam termasuk juga lembaga MTs Islamic Boarding School (IBS) yang berada di bawah nauangan pondok pesantren. MTs Unggulan Al-Qodiri 1 Jember yang berbasis IBS ini sudah melakukan upaya untuk mengatasi ini, salah satunya dengan cara mengintegrasikan nilai-nilai sufistikan dalam kurikulum mata pelajaran. Untuk mendiskripsikan proses integrasi di lembaga tersebut, maka peneliti menggunakan pendekatan penelitian kualitatif dan jenis penelitian studi kasus. Hasil penelitiannya menunjukkan bahwa integrasi nilai-nilai sufistik dalam mata pelajaran di MTs IBS sudah dilakukan dengan baik. Nilai-nilai sufistik yang telah diintegrasikan terdiri dari nilai keikhlasan, kesederhanaan, ukhuwah Islamiyah, kemandirian dan kedisiplinan. Proses integrasi ini dilakukan dengan cara semua nilai sufistik diinternalisasikan dalam beberapa fokus atau sub fokus pembahasan yang berhubungan dengan nilai-nilai lainnya. Integrasi nilai-nilai karakter tersebut dalam kurikulum mata pelajaran dilakukan dalam tiga aspek yaitu kedalam silabus, RPP dan proses pembelajaran. Model integrasi ini dapat mempermudah guru untuk melakukan proses penanaman, pebentukan dan pembiasaan nilai-nilai sufistk dalam kehidupan sehari-hari peserta didik.